Blood lead level and cardiovascular risk factors among bus drivers in Bangkok, Thailand - Orawan Kaewboonchoo (2018)
This study aimed to clarify the role of blood lead level (Pb-B) as one of the cardiovascular risk factors. To evaluate the cardiovascular risk the second derivative finger photoplethysmogram (SDPTG) was used. The subjects comprised of 420 male bus drivers in Thailand. The subjects' age ranged from 20 to 60 yr. Mean age (± standard deviation) were 41.6 (± 7.7) yr. Mean working years was 8.8 (± 6.8) yr. Pb-B ranged from 2.5 to 16.2 μg/dl with the mean Pb-B of 6.3 (± 2.2) μg/dl. The mean of aging index of SDPTG (SDPTG-AI) were -0.50 (± 0.30). The SDPTG-AI increases with age, Pb-B, smoking and alcohol consumption. There was significant correlation between Pb-B and SDPTG-AI after controlling for age, body mass index and lifestyle factors. These results suggest that Pb-B is possibly an independent cardiovascular risk factor for bus drivers exposed to lower level of lead.